FORMATION IN STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS OF THE NEEDS FOR REGULAR PHYSICAL CULTURE CLASSES - Subbota, Yu.V. (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the problem of forming of students of higher educational establishments necessity in regular physical training; to produce the results of awn sociological research; to perform the principal motives of forming of students of necessity in regular physical training.